2002
DOI: 10.1099/0022-1317-83-9-2145
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus core protein represses the p21 promoter through inhibition of a TGF-β pathway

Abstract: The increased proliferation rate of hepatocytes is one of the major risk factors for the development of hepatocellular carcinoma. In this study, we investigated the mechanism by which hepatitis C virus (HCV) core protein represses transcription of the universal cyclin-dependent kinase inhibitor p21 gene in murine fibroblast NIH 3T3 cells. From the transient reporter assays of p21 promoter, we found that the TGF-β-responsive element (TβRE) located between N83 and N74 of the p21 promoter is responsible for the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 33 publications
3
38
0
1
Order By: Relevance
“…In this case, Smad3 activates p21 promoter by its ability to increase the binding of Sp1 protein to this specific Sp1 site (Zhang et al, 1998). In line with these, our results indicate that following TGF-b stimulation, the core protein, but not NS3, represses the binding of the Smad3/Sp1 complex to this specific Sp1 site (Figure 7f), which is consistent with the previous results showing that, with or without TGF-b treatment, the HCV core protein represses the p21 promoter via the Sp1 site (Ray et al, 1998;Dubordeau et al, 2002;Lee et al, 2002c). Thus, the core protein, but not NS3, may interfere with TGF-b-induced p21 promoter activity by disrupting Smad3/Sp1 complex formation or by blocking the DNA-binding affinity of this complex.…”
Section: Discussionsupporting
confidence: 93%
“…In this case, Smad3 activates p21 promoter by its ability to increase the binding of Sp1 protein to this specific Sp1 site (Zhang et al, 1998). In line with these, our results indicate that following TGF-b stimulation, the core protein, but not NS3, represses the binding of the Smad3/Sp1 complex to this specific Sp1 site (Figure 7f), which is consistent with the previous results showing that, with or without TGF-b treatment, the HCV core protein represses the p21 promoter via the Sp1 site (Ray et al, 1998;Dubordeau et al, 2002;Lee et al, 2002c). Thus, the core protein, but not NS3, may interfere with TGF-b-induced p21 promoter activity by disrupting Smad3/Sp1 complex formation or by blocking the DNA-binding affinity of this complex.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, many studies have demonstrated an interaction between viral oncogenic proteins and p21. For example, adenovirus E1A protein, 19 human papillomavirus E7 protein, 20 and hepatitis C virus core protein, 21 each bind to p21 and to the tumor suppressor protein, p53. p21 gene expression has also been shown to be regulated by viral proteins, including hepatitis C virus core protein 22 and HIV-1 Vpr protein.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, viral proteins of HCV seem to be playing the major role in hepatocarcinogenesis. The proteins widely reported to be associated with HCV-mediated hepatocarcinogenesis are core, NS3 and NS5A proteins, which have all been shown to inhibit p21 WAF1 expression post-transcriptionally [41,42,43]. NS4A and NS4B each mediates translational inhibition, and probably increases degradation, of certain cellular proteins [44].…”
Section: Molecular Mechanisms Of Hepatocarcinogenesismentioning
confidence: 99%